Research on communication network system model oriented to the new communication services - WANG Ai-bao1; ZHANG Guang-zhao1 (Tongxin xuebao)
Through the analysis of the capabilities of new communication network taking Internet as representative,the STL system model of new communication network was put forward,which has three dimensions including space domain,time domain and language domain,and was comprised of three elements including transmission capability,memorization capability and computation capability,on the basic of the STL mode,the principle of transformation between the com-munication capabilities was proved. From the interpretation of the current Internet application services,it can be said that the STL mode has certain use for the development of communication theory and network technology.